Effect of waste organic amendments on Populus sp biomass production and thermal characteristics. (August 2016) - Paniagua, S.; Escudero, L.; Escapa, C.; Coimbra, R.N.; Otero, M.; Calvo, L.F.
Abstract: Energy crops and thermal conversion of the obtained biomass is a feasible route for the production of energy. In this work, dehydrated composted sewage sludge (BIOSOLIDS) and sludge from dairy wastewater treatment (MUD) were used as organic amendments on four different poplar clones (UNAL, I-214, AF-2 and AF-8) and. These amendments were yearly applied throughout a four years' study aiming to find out the effects on both agronomic (diameter, height and biomass volume of the trees) and thermal (fuel and thermogravimetric analysis) properties of the poplars. The application of MUD improved the agronomic characteristics of the poplars, especially those of UNAL and AF-2. Thermal results were not as conclusive, but pointed to an improvement of the thermal behavior of UNAL under BIOSOLIDS treatment and of AF-2 and AF-8 under MUD fertilization. On the whole, the most favorable case was that of the AF-2 under fertilization with MUD. Graphical abstract: Highlights: Poplar has potential as energy crop due to its adaptability and high biomass yield. Four different poplar clones were grown during a four years' study. Sludge from urban and from dairy wastewater treatment were yearly applied on poplars. The agronomic effects and thermal properties of biomass were assessed for each clone. The dairy waste amendment combined with the AF2 clone showed the best performance.